Supercomputer technologies in the development of methods for solving inverse problems in ultrasound tomography - Goncharsky, A.V.; Romanov, S.Yu. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2012)
This paper deals with the development of efficient methods for solving inverse problems of wave tomography. An inverse problem is considered as a coefficient inverse problem for the wave equation. Supercomputer technologies allow one to obtain high-resolution tomographic images of diagnosed objects.